Trends in HeartMate 3: What we know so far. Issue 1 (6th November 2019) - Lanfear, Allison T.; Hamandi, Mohanad; Fan, Joy; DiMaio, J. Michael; George, Timothy J.
Abstract: Background: The HeartMate 3 left ventricular assist device (LVAD) is a novel, intrapericardial, centrifugal‐flow pump with a fully magnetically‐levitated rotor designed to provide hemodynamic support in patients with end‐stage heart failure. Unique aspects of this LVAD have allowed for improved hemocompatibility and the development of minimally‐invasive implantation techniques. Methods: The PubMed, EMBASE, and Google Scholar databases were searched for publications relating to the HeartMate 3 device, with a focus on hemocompatibility related outcomes, anticoagulation management, and surgical techniques. Results: Nine articles analyzing hemocompatibility related outcomes from two clinical trials, two clinical studies, and one registry series were identified. Conclusion: HeartMate 3 has reduced the rate of disabling stroke and pump thrombosis. However, despite increased hemocompatibility due to specialized design features, the residual risk of both surgical, and gastrointestinal bleeding remains a major adverse outcome. Different anticoagulation management and surgical techniques have been evaluated to address the remaining complications.